Effect of Information Genotype on Investors' Inertia - Fatemeh Jahandari; Amirhossein Taebi Noghondari; Hadis Zeinali (Journal of Asset Management and Financing)
Investors' belief that current market conditions will persist often leads them to delay reacting to earnings information. Conversely, companies may disclose information in different patterns to significantly impact stock prices and influence investor decisions. They may reveal positive and negative news sequentially or all at once. This study investigated the effects of the order and pattern of information presentation (information genotype) on investor inertia. The sample included data from 5 industries and 58 companies listed on the Tehran Stock Exchange (TSE) from 2010 to 2014. Linear regression analysis based on panel data methods was conducted using EViews and Excel software to test the hypotheses. The findings indicated that information genotype had a positive and significant effect on investor inertia. However, while the sequence of negative to positive information had a direct and significant impact on investor inertia, the sequence of positive-to-negative information did not significantly affect investor inertia.Keywords: Information Genotype, Investors' Inertia, Market Sentiment Index, Standard Unexpected Earnings.Classification JEL: G11-G41-G4-G14 IntroductionDisclosure of information is considered in terms of its content, timing, and presentation method (Haqiqat & Iranshani, 2010). Previous studies have focused on the impact of information content and its timing on investors' decisions, but have paid less attention to the form of information presentation (Sheari Anaqiz et al., 2023). Today, companies often disclose information sequentially rather than simultaneously, while the pattern of information presentation can affect information overload, cognitive effort, and decision-making (Rafay & Farid, 2018). Understanding the effect of information presentation models is important for investors facing a wide range of information to make optimal decisions. This study investigated the effects of information genotype on investor inertia, which are emerging areas of study globally. The innovation of this study was that it examined 3 different scenarios dealing with the effects of - a sequence of positive-to-negative information, a sequence of negative-to-positive information, and simultaneous disclosure of good and bad news - on investor inertia. According to classical finance theory, people should react to information in a similar way regardless of how it is presented as the underlying content is the same (Aprayuda, 2021). However, in financial decision-making, the way information is processed, in addition to how it is presented, can affect investor behavior. The belief adjustment theory suggests that when the information genotype is such that positive news is published first followed by negative news, or vice versa, investors will revise their prior beliefs. The information published first will receive less attention than the more recent information due to the "recency effect" (Samal & Mohapatra, 2020). The "primacy effect" also indicates that investors are more sensitive to the first news published (Samal & Mohapatra, 2020). Furthermore, prospect theory suggests that investors may remain in their current position and hold their stocks when bad news is published due to loss aversion (Cui & Zhang, 2022).The information processing theory posits that when investors are bombarded with large amounts of information, their cognitive limitations may prevent them from adequately analyzing the information, leading to suboptimal decision-making. Based on these theoretical perspectives, the central hypothesis of this study was that information genotype has a significant effect on investor inertia. Materials & MethodsTo examine the effect of information genotype, i.e., the order and sequence of information presentation, the study analyzed Average Abnormal Returns (AAR) and Cumulative Average Abnormal Returns (CAAR) under two scenarios: a) Before the news announcement when the order of news is either good news followed by bad news or bad news followed by good news, b) After the news announcement when the order of news is either good news followed by bad news or bad news followed by good news. The independent variable "information genotype" was calculated as the actual deviation from the expected number of executions:  The dependent variable "inertia" was calculated using two measures - the Unexpected Profit Index (UPI) and the market Sentiment Index (SENTI):                        The following regression models were used to evaluate the hypotheses:   The independent variable "information genotype" was proxied by 3 scenarios: 1) Positive-to-negative consecutive information, 2) Negative-to-positive consecutive information, and 3) Simultaneous information (good and bad news). The dependent variable "investors' inertia" was proxied by 2 measures: 1) Market sentiment index and 2) Unexpected profit. To select the control variables, the researchers reviewed prior studies related to information genotype and investor inertia. The control variables include company size, financial leverage, and return on assets. FindingsThe regression coefficient associated with the sequence index of negative to positive information is 0.752, with a significance level of p = 0.0107 (p < 0.1). Consequently, at the 10% significance level, the second hypothesis is supported, indicating that the transition from negative to positive information significantly influences the market sentiment index. In contrast, the regression coefficient for the sequence index of positive to negative information is -0.605, with a significance level of p = 0.036 (p < 0.1). Thus, at the 10% significance level, the fourth hypothesis is confirmed, revealing a significant negative relationship between positive to negative information and the market sentiment index. The regression coefficient that reflects the simultaneous effect of negative and positive information is -0.012, with a significance level of p = 0.924 (p > 0.1). Therefore, the sixth hypothesis is not supported, indicating that there is no significant relationship between the simultaneous variables of positive and negative information on the market sentiment index. Furthermore, the regression coefficient for the sequence index of negative to positive information is 0.576, with a significance level of p = 0.0502 (p < 0.1). This implies that the influence of negative to positive information on unexpected profit is significant, thereby confirming the third hypothesis. Conversely, the regression coefficient for the sequence index of positive to negative information is -0.660, with a significance level of p = 0.022 (p < 0.1). Hence, the fifth hypothesis is also confirmed, as there is a significant relationship between the sequence of positive to negative information and unexpected profit. Lastly, the regression coefficient for the combined effect of negative and positive information is 0.009, with a significance level of p = 0.952 (p > 0.1). Therefore, the relationship between the simultaneous variables of positive and negative information on unexpected profit is insignificant, leading to the conclusion that the seventh hypothesis is not supported. Discussion & ConclusionThe findings from the three different scenarios investigated in this study provided insights into the underlying behavioral theories that explained investor inertia. Perspective theory suggested that investors tended to sell losing stocks faster than profitable ones driven by excessive reaction and loss aversion. This behavioral bias led to increased investor inertia, causing them to sell stocks and exit the market. This hasty decision-making hurt market sentiment and prevented investors from earning unexpected profits. In contrast, belief adjustment theory explained that when negative news was followed by positive news, investors revised their previous beliefs and became optimistic about the stock's future growth potential. This positively influenced investor inertia, leading them to hold onto the stocks in anticipation of higher future returns. As a result, investors were able to earn unexpected profits and market sentiment improved. However, the information processing theory indicated that when good and bad news were released simultaneously, investors' inherent limitations in processing large amounts of information impaired their ability to analyze the news effectively. This affected investor inertia, causing them to remain indifferent and not react. Consequently, market sentiment declined and investors failed to earn unexpected profits. Based on the resutls, one of the key conclusions was that the genotype of information, i.e., the order and sequence of news presentation, had a significant impact on the inertia of investors. This underscored the importance of understanding the behavioral biases and decision-making processes that drove investor behavior in response to different information environments.